Anion-dependent assembly of Dy complexes: structures and magnetic behaviors1. Issue 27 (21st July 2015) - Chen, Peng; Zhang, Meiqi; Sun, Wenbin; Li, Hongfeng; Zhao, Lang; Yan, Pengfei
<x xml:space="preserve">Abstract</x> The in situ reaction of 2-aldehyde-8-hydroxyquinoline, histamine and LnX3·6H2O (X− = OAc−, NO3− and ClO4−) affords three distinct species of eight lanthanide complexes.